Factors Influencing CO2 Emissions and Strategies for Emissions Reduction in Malaysian Transportation Sector - S.I, Mustapa; H.A, Bekhet (International Journal of Engineering and Technology, 2018)
The rapid urbanisation and economic growth has led to unprecedented increase in CO2 emissions, which led to a vital global issue due partly to the rise in demand from the transport sector. In the years ahead, the transport services demand is likely to increase further, which lead to intensification in CO2 emissions as well. The transportation sector in Malaysia contributes for about 28% of total CO2 emissions, of which 85% of it goes to road transportation mode. This has led to a great interest in how the CO2 emissions in this sector can effectively be reduced. Using a multiple regression model and datasets from 1990 to 2015, this study aimed to examine factors that influence the CO2 emissions in Malaysia. Key factors of CO2 emissions, i.e., fuel consumption (FC), distance travel (DT), fuel efficiency (FE), and fuel price (FP) were investigated for the road transport sector. The findings demonstrated that the impact of factors on CO2 emissions were varies in each technology vehicles. These findings not only contributes to enhancing the current literature, but also provide insights for policy maker in Malaysia to design policy instruments for road transport sector.